Analysis of NPM Based Public Policy to Enhance Sustainability Performance: A Grounded Theory - Maryono, Bambang Edy; Handoko, V. Rudy; Maduwinarti, Ayun; Gusmao, Cristino (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study aims to explore the impact of applying New Public Management (NPM) principles on sustainability performance at Perumdam Batiwakkal, Berau Regency, focusing on operational efficiency, service quality, and environmental management. The theoretical framework integrates key NPM concepts privatization, decentralization, and performance measurement based on results with environmental sustainability models to offer a comprehensive understanding of managerial and operational impacts. Utilizing a Grounded Theory approach, data were collected through in-depth interviews with senior management, operational staff, and service users. Data analysis involved open coding, axial coding, and selective coding to develop a conceptual framework on NPM application and sustainability performance. Findings indicate that while NPM principles can enhance operational efficiency and service quality, challenges persist in achieving full sustainability performance. Key factors influencing effectiveness include leadership support, resource availability, and policy adaptation. The study provides insights into adapting NPM principles to improve sustainability performance and offers practical solutions for implementation challenges.